Study on determinants that influence female behavior towards purchasing intention of international fashion brands - Haslina, Abu Bakar (Universiti Malaysia Sarawak (UNIMAS), 2011)
This study describes the indicators that influence the intention of female students to purchase international fashion brands. This study emphasizes the three main indicators which are demographics, personal values and social status, and purchase intention as dependent variable. This study is based on analysis of data obtained from 376 female students from three selected higher education centre in penang.) Analyses are based on descriptive analysis, correlation and regression to identify the relationship between demographic, personal values and social status with purchase intention toward international fashion brands. The study reveals that female students define international fashion brands as a best quality, expensive and exclusive. There were significant relationship between personal values and social recognition with purchase intention. However, demographic was found no significant related with purchasing intention. Therefore, international fashion brand marketers are able to use this information in order to determine the right place, price, product and promotion.